Réfugiés de la guerre civile grecque en Roumanie : moyens de communication, activité éditoriale, production radiophonique - Christina Alexopoulos (Cahiers Balkaniques, 2017)
The Greek communists living in exile in different socialist republics during or after the Greek Civil War published their works under conditions that were very different from those faced by the communists who remained in Greece, forced into clandestinity, although both groups felt the weight of various forms of censorship or auto censorship. An examination of the editorial and radiophonic activities of Greek communists in the Eastern Bloc can help us to better discern the ideological positions and the political objectives that determined the refugees’ discourse and communication practices. We begin by situating the refugees’ politics of communication, firstly in relation to their publication experience during the civil war, when the center of editorial and radiophonic activities had shifted to Bucharest; secondly, in relation to the evolution of their editorial activity in Romania in the 1950’ and 1960’; and, finally, in highlighting their radiophonic activities of the same period. The refugees’ production (be it journalistic, radiophonic, or literary works) in each host country demonstrates a strong internal coherence. If there is a production specific to each host country, we can nevertheless discern a larger difference between the totality of the works produced in exile and the editorial and radiophonic activities of the communists who remained in Greece. The first often expresses a certain sacralisation of the past, cut off from the contemporary political changes taking place in Greece; the latter is much less attached to Party orthodoxy. Even if they are oriented towards Greece and suspended in time, the works produced in exile are not impermeable to the evolutions taking place in the different Eastern Bloc countries. At the same moment, they attempt to keep their focus on Greece, whereas the editorial and radiophonic activities of the Greek Left seem to better integrate the memory of the civil war in their narration of the country’s history and in their response to the stakes of the contemporary political situation.